Controle da maturação e conservação pós-colheita de mamão 'golden' sob 1-metilciclopropeno, fotocatálise heterogênea e refrigeração - Silva, Josilene Amaro da (2014)
Papaya is a climacteric fruit that presents rapid loss of quality after harvest due to the rapid maturation, which results in loss of firmness and incidence of fungi. The use of 1-methylcyclopropene (1-MCP) has been effective in controlling the ripening of climacteric fruits. The combination of 1-MCP with alternative methods that can delay fruit ripening and reduce the use of pesticides in the control of fungal diseases in post harvest may allow reduction of doses of 1-MCP and provide greater efficiency in the control of maturation without prejudice to the quality of the fruit. The heterogenous photocatalysis (HF) has been used to reduce the microbial load of the air into indoor and refrigerated environments. However, the influence of the application of 1-MCP on changes in papayas functional potential need further exploration to ensure maintenance of quality during papaya postharvest life. This study was conducted in two experiments. In the first experiment it was evaluated the influence of application of 100 nL.L-1 1-MCP followed by storage under FH on the maintenance of „Golden‟ papaya. Papayas harvested at maturity stage 1 (1 of 15% of yellow coloration of the skin) were treated with 1-MCP and control (no 1-MCP) and stored at 12 ° C and 72 ± 1 and 82 ± 2% RH, into ambient with and without FH. The evaluations were performed as physic-chemical aspects, bioactive compounds, enzymatic activities of pectinmethylesterase, polygalacturonase, and sensory were carried out during 27 days of storage at staggered intervals between three and six days. The use of 1-MCP delayed in 14 days ripening of papaya 'Golden' stored at 12 ° C. Based on the acceptance limit, the 'Golden' papaya was suitable for consumption after 21 days to fruit treated with FH, with or without 1-MCP, 16 days for fruit treated with 1-MCP, and for 7 days for the control. Therefore, the use of 1-MCP + FH increased in 14 days the postharvest life of 'Golden' papaya. The second experiment evaluated the influence of application of 1-MCP in 100 nL.L-1 in 'Golden' papaya stored under refrigeration and room conditions in the bioactive compounds and antioxidant activity. Papayas treated for 12 hours with 100 nL.L-1 1-methylcyclopropene (+MCP) and control (-MCP) were stored at 12 ± 1 ° C and 82 ± 2% RH and 23 ± 2 °C 72 ± 4% RH and evaluated for the contents of ascorbic acid, total chlorophyll, carotenoids anthocyanins, and yellow flavonoids, and antioxidant activity (TAA) by the DPPH radical. The content of ascorbic acid and carotenoids increased during storage in papayas treated with 1-MCP, regardless of storage temperature. The yellow flavonoids increased in fruit kept under refrigeration, but were lower than papayas treated with 1-MCP. In turn, anthocyanins and TTA were higher in fruit treated with 1-MCP. Therefore, the application of 1-MCP does not compromise the supply of bioactive compounds and functional potential of „Golden‟ papaya during storage.